2019
DOI: 10.1080/1369183x.2019.1683442
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and household spending strategies: evidence from the Life in Kyrgyzstan Study, 2011–2013

Abstract: Globalised labour migration and remittances can help alleviate household poverty and provide supplemental income in many countries. Kyrgyzstan, like other Central Asian countries, has experienced dramatic geopolitical changes, economic reform, and rapid demographic shifts in the post-Soviet-Union era. Based on measurements of GDP, it is one of the most remittancedependent countries in the world. This study uses data from the Life in Kyrgyzstan Study collected from 2011 to 2013 to break down household budgets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…This information allows us to allocate changes in aggregate consumption when we conduct simulations for remittance shock scenarios using the I-O model. We estimate the consumption equations closely following the empirical specification of Wang, Hagedorn, and Chi (2021), with some additional assumptions about how income from remittances is allocated and utilized in a remittance-receiving household:…”
Section: Step 1: Micro-level Analysis Of Household Spending and Savin...mentioning
confidence: 99%
See 2 more Smart Citations
“…This information allows us to allocate changes in aggregate consumption when we conduct simulations for remittance shock scenarios using the I-O model. We estimate the consumption equations closely following the empirical specification of Wang, Hagedorn, and Chi (2021), with some additional assumptions about how income from remittances is allocated and utilized in a remittance-receiving household:…”
Section: Step 1: Micro-level Analysis Of Household Spending and Savin...mentioning
confidence: 99%
“…The coefficient, 𝛽 , refers to the percentage point change in the share of expenditure item 𝑖 in total expenditure given a percentage change in total household income. Unlike Wang, Hagedorn, and Chi (2021), who distinguish between remittance and non-remittance income by obtaining a unique parameter of marginal propensity to consume for each income, we use household's 𝑇𝐼𝑛𝑐 or total income (in log) regardless of sources. In other words, we assume that remittance income is as fungible as all other sources of income, such as wages and salaries.…”
Section: Step 1: Micro-level Analysis Of Household Spending and Savin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ahunov et al (2015) did not find a significant income effect for remittances on educational spending in Uzbekistan. Wang et al (2019) also found that remittances have no effect on investment in education and housing;…”
Section: Introductionmentioning
confidence: 97%
“…Это множественное планирование будущего «здесь» и «там», влияние денежных переводов на домохозяйства на родине, положение киргизских мигрантов в иерархии по сравнению с другими сообществами и др. (Джанызакова 2019;Reeves 2012;Gerber, Zavisca 2020;Wang et al 2021).…”
unclassified